Knowledge and trust of mothers regarding childhood vaccination in Rwanda - Mbonigaba, Edward; Yu, Fengyun; Reñosa, Mark Donald; Cho, Frederick Nchang; Chen, Qiushi; Denkinger, Claudia M.; McMahon-Rössle, Shannon A.; Chen, Simiao (BMC public health, 2024)
Knowledge and trust are some of the contributing factors to vaccine acceptance(VA) and Vaccine hesitancy (VH) is one of the top threats to global health. A significant drop in childhood vaccination has been observed in recent years. One important reason that influences mothers' choice to either postpone or avoid children's vaccinations is knowledge and trust in childhood vaccines. This study aimed to assess mothers' knowledge and trust on vaccination of their children, and to examine the association between vaccination knowledge and selected socio-demographic factors.
Online veröffentlicht: 17. April 2024
Gesehen am 10.10.2024